The Effect of General and Vocational High School Quality on Labor Market Outcomes in Indonesia - Rizqi Qurniawan; Thia Jasmina (Pusbindiklatren Bappenas, 2021)
To improve the quality and competitiveness of human capital and correspond to the Sustainable Development Goals (SDGs) 4 especially target 4.3, to ensure equal access for all women and men to affordable and quality technical, vocational and tertiary education, Indonesia has been focusing on improving the quality of secondary education. However, empirical data and previous research showed that secondary school graduates in Indonesia face high unemployment and income differences, especially vocational school graduates. The quality of secondary high schools plays an important role in determining the years of schooling of the graduates and indirectly impacts labor market outcomes. Using longitudinal panel data at the individual level from the Indonesia Family Life Survey (IFLS) of 2000, 2007, and 2014; and applying education production function and Mincer earning equation, this study finds that the difference in wages between graduates of general and vocational high schools is not statistically significant despite the school quality. However, analyzing within the vocational high schools shows that better quality of vocational high schools increases years of schooling of its graduates as they can access tertiary education, and subsequently increases their performance in the labor market. This finding indicates that policies to improve school quality, especially vocational high schools, should be enhanced.